An MFS Transporter-Like ORF from MDR Acinetobacter baumannii AIIMS 7 Is Associated with Adherence and Biofilm Formation on Biotic/Abiotic Surface. (20th February 2012) - Sahu, Praveen K.; Iyer, Pavithra S.; Gaikwad, Madhumita B.; Talreja, Sheetal C.; Pardesi, Karishma R.; Chopade, Balu A.
Abstract : A major facilitator superfamily (MFS) transporter-like open reading frame (ORF) of 453 bp was identified in a pathogenic strain Acinetobacter baumannii AIIMS 7, and its association with adherence and biofilm formation was investigated. Reverse transcription PCR (RT-PCR) showed differential expression in surface-attached biofilm cells than nonadherent cells. In vitro translation showed synthesis of a~ 17 kDa protein, further confirmed by cloning and heterologous expression in E. coli DH5α . Up to 2.1-, 3.1-, and 4.1- fold biofilm augmentation was observed on abiotic (polystyrene) and biotic ( S. cerevisiae /HeLa) surface, respectively. Scanning electron microscopy (SEM) and gfp -tagged fluorescence microscopy revealed increased adherence to abiotic (glass) and biotic ( S. cerevisiae ) surface. Extracellular DNA(eDNA) was found significantly during active growth; due to probable involvement of the protein in DNA export, strong sequence homology with MFS transporter proteins, and presence of transmembrane helices. In summary, our findings show that the putative MFS transporter-like ORF ( pmt ) is associated with adherence, biofilm formation, and probable eDNA release in A. baumannii AIIMS 7.